Computer Science & Technology Series : XX Argentine Congress of Computer Science. Selected papers - Feierherd, Guillermo Eugenio (2015)
CACIC’14 was the twentieth Congress in the CACIC series. It was organized by the Department of Engineering and Technological Research at the La Matanza National University in La Matanza, Buenos Aires. The Congress included 13 Workshops with 135 accepted papers, 3 Conferences, 3 technical panels, 2 invited tutorials, different meetings related with Computer Science Education (Professors, PhD students, Curricula) and an International School with 6 courses. CACIC 2014 was organized following the traditional Congress format, with 13 Workshops covering a diversity of dimensions of Computer Science Research. Each topic was supervised by a committee of 3-5 chairs of different Universities. The call for papers attracted a total of 230 submissions. An average of 2.5 review reports were collected for each paper, for a grand total of 594 review reports that involved about 206 different reviewers. A total of 135 full papers, involving 445 authors and 78 Universities, were accepted and 24 of them were selected for this book.